Model Pembelajaran Example Non-Example terhadap Kemampuan Matematika pada Materi Pecahan Siswa Kelas II SD - Eva Fauziah (Universitas Pendidikan Indonesia (UPI), 2022)
The inability of students to divide material into fractions for mathematics subjects is the background for research on the effect of the Example Non-Example learning model on mathematical abilities in class II student fractions. This research uses a quantitative approach, the Quasi-Experimental Design method. The result of the research is that there is an influence of the Example Non-Example learning model on the mathematical ability of fraction material for second grade elementary school students. It has been proven that there is an influence from the Example Non Example learning model used in the experimental class on the ability to divide fractional material as seen from the t-test results.